2009
DOI: 10.1108/10650750911001860
|View full text |Cite
|
Sign up to set email alerts
|

The new Papers Past: an international collaboration between New Zealand, India, Germany, and the United States

Abstract: PurposeThe purpose of this paper is to discuss international collaboration on the Papers Past historic newspaper digitisation project, with particular focus on how to work together across four countries for a successful outcome.Design/methodology/approachThe paper outlines the stages of the project and provides project perspectives from all the partners. Concludes with lessons learned.FindingsThe article confirms that clear communication and requirements are essential to any collaborative project.Originality/v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Insufficient communications amongst all the project stakeholders is an anathema to project success. My co-authors and I wrote about a software and digital conversion project with team members from four different countries and five different organizations (Lanz, 2009). We found that frequent, clear, and open communication between team members was fundamental to the project's success.…”
Section: Inappropriate Skillsmentioning
confidence: 96%
“…Insufficient communications amongst all the project stakeholders is an anathema to project success. My co-authors and I wrote about a software and digital conversion project with team members from four different countries and five different organizations (Lanz, 2009). We found that frequent, clear, and open communication between team members was fundamental to the project's success.…”
Section: Inappropriate Skillsmentioning
confidence: 96%
“…Many news archive systems are built on a single-media model (all newspapers (e.g. [2], [17]) or all news broadcasts from one TV station (e.g. [19]).…”
Section: News-specific Systemsmentioning
confidence: 99%